Guidance and Counseling on Juvenile Delinquency for Students at SMPN 1 Arahan, Indramayu Regency - Muhamad Ikhwanarofiq (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
Often in this search for identity, teenagers tend to hang out with the wrong people and do deviant things which are usually called juvenile delinquency. Observing this phenomenon, by distributing sociometric questionnaires and counseling on juvenile delinquency at the Arahan Lor Village Junior High School which aims for us and the BK teacher to be able to find out about friendships and also to be able to raise awareness and educate junior high school teenagers to be able to stay away from and stop doing various kinds of delinquency that have occurred, not only has an impact on the health that will be faced but will have an impact on the laws in force in Indonesia. With the Communicative activities method, students are required to listen actively, where the speaker or participant repeats the words conveyed with one-way or two-way communication. It is hoped that after this counseling activity, teenagers can understand the dangers of deviant behavior and not do deviant behavior again. Problems that arise among teenagers that can be categorized as serious problems include the problem of juvenile delinquency, considering that teenagers are an age group that is expected to be the next generation in the future. Counseling guidance aims to help individuals realize themselves as whole human beings in order to achieve happiness in life in this world and in the hereafter. From the results and achievements of the Juvenile Delinquency Counseling activities in the Perspective of Law and Health, it can be concluded that adolescence is a period that must be considered, initially during this period emotional and mental instability often occurs. Because this is what underlies adolescents to carry out deviant behavior, so that it becomes the main problem in society, it is necessary to hold juvenile delinquency counseling education reviewed from a legal and health perspective to provide knowledge to adolescents about the problem of juvenile delinquency seen from its impact and its connection to health and applicable laws.